Comparison between sevoflurane and propofol induction in I-gel insertion in pediatric patients undergoing inguinal herniotomy - Harshita Singh; Harpreet Kaur; Shirin Parveen; Narendra Singh Bafila; Kirtika Yadav; Anam Rizwan; Dhruvraj Singh (Asian Journal of Medical Sciences)
Background: Supraglottic airway devices are crucial in pediatric anesthesia for their ease of use, reduced trauma, and minimal hemodynamic disturbance. The I-gel device offers a secure airway seal without the need for an inflatable cuff, making it ideal for pediatric patients by minimizing airway trauma and postoperative sore throat.